(untitled) (Research, Society and Development, 2022)
Introduction: Schizophrenia is a severe, episodic and persistent disease with a characteristic time course in which acute episodes, characterized by positive psychotic symptoms such as delusions and hallucinations, are followed by a chronic phase in which disabling negative and cognitive symptoms and impairments social groups tend to be prominent. The amino acid glutamate is the main excitatory neurotransmitter of the central nervous system (CNS), present in approximately 30 to 40% of brain synapses and in 80% of areas involved in cognitive processes, mainly in the cerebral cortex and hippocampus. Objective: to demonstrate the glutamatergic hypothesis in the pathophysiology of schizophrenia. Methodology: This is an integrative literature review, and the search was performed through online access in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Google Scholar, Virtual Health Library (BVS) and EBSCO Information Services, September 2021. Results and discussion: The relationship of glutamatergic neurotransmission with the symptoms presented by schizophrenic individuals can be validated by evaluating the close interaction between NMDA glutamate receptors in the mesocortical pathway, responsible for normal cognitive functions and motivation, and the consequent release of dopamine. In situations of hypofunction of the glutamate pathway, there is little release of dopamine in the cortex, which results in negative and cognitive symptoms. Conclusion: a lot of evidence suggests the involvement of NMDA-type glutamatergic receptors in schizophrenia.